CameraIcon
CameraIcon
SearchIcon
MyQuestionIcon
MyQuestionIcon
Question

Simplify (a3b3a2+b2+ab) is equal to

A
ab
Right on! Give the BNAT exam to get a 100% scholarship for BYJUS courses
B
a+b
No worries! We‘ve got your back. Try BYJU‘S free classes today!
C
a2b2
No worries! We‘ve got your back. Try BYJU‘S free classes today!
D
1
No worries! We‘ve got your back. Try BYJU‘S free classes today!
Open in App
Solution

The correct option is A ab
We know that one of the algebraic formula is a3b3=(ab)(a2+b2+ab), therefore, we solve the given expression

=a3b3a2+b2+ab using the above formula as shown below:

=a3b3a2+b2+ab

=(ab)(a2+b2+ab)a2+b2+ab
=ab

Hence, a3b3a2+b2+ab=ab.

flag
Suggest Corrections
thumbs-up
0
mid-banner-image
mid-banner-image
similar_icon
Related Videos
thumbnail
lock
Algebraic Identities
MATHEMATICS
Watch in App